Legal Liability for Issuance of Promissory Note - Zulfikri Zulfikri (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Promissory notes/promissory notes at the beginning of their development were only recognized as a means of acknowledging debt, but later the promissory notes turned into promissory notes which have the power as securities/negotiable instruments, so that they can function as a medium of exchange for trade in goods and services in the community. The purpose of this study was to analyze legal liability for the issuance of promissory notes. The research method used is normative juridical research. The legal materials used are primary and secondary legal materials. The data collection technique used is literature study related to promissory notes from primary and secondary legal materials. Then the data will be analyzed using qualitative analysis, namely by observing the data and then taking things that can be related to the promissory note from the data that has been collected. The results of this study are promissory notes or acceptance letters are letters of willingness or agreement to pay a certain amount of money to the holder or his successor on a certain day. In Indonesia, the provisions regarding promissory notes or promissory notes are regulated in articles 174 – 177 of the KUHD, where according to the KUHD, this instrument carries a high risk, because in its implementation it does not require a guarantee, therefore for parties who use this instrument as a business activity must be careful heart.